Oxidative stress in experimental vitiligo C57Bl/6 mice - Jalel Akrem; Yassine Mrabet; Hamdaoui Mohamed (Wolters Kluwer Medknow Publications, 2009)
Aim: To evaluate whether oxidative stress is implicated in melanocyte damage in vitiligo. Background: Vitiligo is a complex disorder characterized by gradually enlarging areas of depigmentation. A new unifying hypothesis for the etiology of this pigment disorder is proposed, in which we postulate that the final destruction of melanocytes in vitiligo results from a cascade of reactions initiated by a disregulation of melanogenesis, as the result of a breakdown in free radical defense. Methods : We evaluated 18 vitiligo mice and 12 controls that were age matched. Parameters of oxidative stress such as catalase (CAT), superoxide dismutase (SOD), and plasma malondialdehyde (MDA) were measured by spectrophotometry. Results: MDA levels in vitiligo mice were significantly higher than in controls ( P < 0.001). CAT, SOD, and glutathione peroxidase (GPx) activities in mice were significantly lower than controls ( P < 0.05 and P < 0.001, respectively). Conclusion : Our results confirmed that oxidative stress plays an important role in the pathogenesis of vitiligo. Melanocyte damage in vitiligo might be linked to generalized oxidative stress. This study is the first report on antioxidant parameters in experimental vitiligo mice.